Study on potential of multipurpose desk for small space hostel in Universiti Malaysia Kelantan (UMK) - Mohd Salahuddin, Nur Izzati (2019)
The evolution of Malaysia's education has leads to increase in the construction of universities and polytechnics apart from a variety of schools building. Education places usually provide dormitory or hostel and this types of living place surely have limited space as they are all designed in same pattern at once. Usually, students have issues on limited space might affect their interest in study at workstation. So this thought has led to the research which to determine the potential of the multipurpose desk in small space hostel. The study used a survey method using a questionnaire to collect data from the respondents. 175 respondents were involved in this study which were form University Malaysia Kelantan students. Data that have been collected are then entered and analysed using SPSS version 25.0. The method used is 'Descriptive statistics (Mean)', 'Cross-Tabulation' and 'Reliability test'. Analytical results indicate that the level of acceptance in strength and weakness of existing desk is respondents are agree with value of mean 3.53 and 3.74 respectively. Therefore, students in UMK received good perception on new value added multipurpose desk to being accepted by students is agree with Model A, with 86 out of 175 votes from four models. So with this study done, the multipurpose desk with ergonomics element contribute the space saving furniture for students and interior design industry while applying correct posture adoption among students.